Enron and internationally agreed principles for corporate governance and the financial sector - Cornford, Andrew (UN New YorkUS, 2004)
Contains an account of the breakdown of corporate governance, in a recent scandal, that involved the collapse of Enron. This involved not only conflicts with standards for good corporate governance but also unusually extensive use of sophisticated techniques and transactions to manipulate the firm's financial reports.